2021
DOI: 10.1016/j.jtumed.2021.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical meritorious anticancer effects of Metformin against breast cancer: An In vivo trial

Abstract: Objective This research aims to evaluate the preclinical meritorious and anticancer effects of Metformin in a Xenograft model of breast cancer. Methods This interventional trial was conducted during a defined period of 5 months (August 2016 January 2017). We used a Xenograft model of nude BALB/c mice. A sample size of 50 mice, allocated into two groups and designated as Group A and Group B for Metformin and negative control groups, respectively. The anticancer activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Hence, targeting OXPHOS in cancer cells may be a promising attitude toward cancer therapy. A previous study on MCF-7 cells and a total sample size of 50 athymic BALB/c mice showed that on day 7 of treatment, the tumor size of all the samples reached 100 mm 3 [ 23 ], just like what our results indicate.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Hence, targeting OXPHOS in cancer cells may be a promising attitude toward cancer therapy. A previous study on MCF-7 cells and a total sample size of 50 athymic BALB/c mice showed that on day 7 of treatment, the tumor size of all the samples reached 100 mm 3 [ 23 ], just like what our results indicate.…”
Section: Discussionsupporting
confidence: 86%
“…The sample size was calculated by the ‘resource equation’ technique as defined by [ 22 ]. According to [ 23 ], Group A was assigned to receive metformin 150 mg/kg/day (IP injected), and Group B was assigned to receive 30 mL/kg/day PBS (IP injected) for 14 days. The number of 5 × 10 6 4T1 breast cancer cells was suspended in 100 μl of PBS mixed with 50% Matrigel (BD Biosciences) and infused into the back of the right flank of the mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biguanide metformin, an inhibitor of gluconeogenesis 12 14 and the most prescribed diabetes drug worldwide 15 , has been by far the most popular antihyperglycemic approach used for cancer. At supra-pharmacologic doses – several orders of magnitude higher than in human patients – metformin is capable of reducing breast cancer cell proliferation 16 19 , and slowing tumor growth in vivo in rodents 20 22 . Metformin is safe and shows good target engagement in women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The biguanide metformin, an inhibitor of gluconeogenesis (12)(13)(14) and the most prescribed antidiabetes drug worldwide (15), has been by far the most popular antihyperglycemic approach used for cancer. At supra-pharmacologic doses -several orders of magnitude higher than in human patients -metformin is capable of reducing breast cancer cell proliferation (16)(17)(18)(19), and slowing tumor growth in vivo in rodents (20)(21)(22). Metformin is safe and shows good target engagement in women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%